Investigating the Effect of Gross Capital Formation on Carbon Emissions in Somalia - Nur, Abdirahman Mohamed; Adan, Ahmed Hassan; Ahmed, Ahmed Dahir; Gutale, Ali Abdukadir Ali; Ali, Ali Yassin Sheikh; Dalmar, Mohamed Saney (International Journal of Energy Economics and Policy, 2024)
The advent of climate change has evolved into a paramount challenge for humanity, prompting extensive endeavors to mitigate its consequences. This research delves into the influence between gross capital formation (GCF) and carbon dioxide emissions in Somalia, spanning the years 1991-2019. To scrutinize the long-term associations among the variables under consideration, the study employed autoregressive distributed lag (ARDL) model. Additionally, to ensure the robustness of the study, both dynamic ordinary least squares and fully modified ordinary least squares were applied. Contrary to expectations, the findings indicate that GCF does not exert a significant influence on carbon dioxide emissions. The study advocates for the implementation of a comprehensive environmental policy framework that considers a spectrum of contributing factors beyond GCF. To address the multifaceted nature of environmental challenges, the study recommends initiatives such as diversification of energy sources, technology transfer, promotion of sustainable practices, and integration of climate resilience.